Analysis of MSME Business Sustainability in Mojolaban District, Sukoharjo Regency - Mia Aprilia; M. Iqbal Taufiqurrahman Sunariya (International Journal for Disaster and Development Interface, 2022)
Mojolaban sub-district is one of the sub-districts in Sukoharjo which has the highest MSME business compared to other sub-districts, namely 42 types of MSME. MSME has been running for generations for the last 10 years. During the last 10 years, the income level of Mojolaban District has decreased due to weak consumer purchasing power. One of them is the MSME gamelan in Wirun Village which has decreased until it stops producing. The spatial planning strategy needs to be carried out to restore the income of the residents of Mojolaban District, so it is expected to be able to contribute either directly or indirectly to the economy of MSME owners in Mojolaban District. The aims of this study are to find out the distribution pattern of industry in Mojolaban sub-district, to analyze the level of industrial business sustainability in Mojolaban sub-district, to analyze the industrial business sustainability strategy in Mojolaban sub-district. This research method uses a qualitative deductive method using a field survey. The population and the number of samples used are 80 people consisting of tile MSME, brick MSME, fish MSME, and alcohol MSME. Data collection uses primary and secondary data. Primary data consists of surveys and interviews, while secondary data is obtained from government agencies, published journals, the internet, and from existing research. The analytical method used is spatial analysis and quantitative descriptive analysis. The results of this study indicate that the distribution pattern of the tile, brick, and alcohol MSME businesses has a clustered distribution pattern, while the fish MSME business has a random pattern. The level of sustainability of the roof tile MSME business is 56.35%, the brick MSME business continues at 58.3%, and the fish and alcohol MSME business shows 100% continuous. The strategy for the sustainability of the title MSME business is to improve the quality of production, increase the amount of production and maintain good production quality. The strategy carried out by the alcohol MSME business is to maintain the quality of production. Meanwhile, the fish and brick MSME business strategy is carried out by increasing the number of workers and the quality of production.